Eclampsia in Janakpur Zonal Hospital, Nepal: Favourable outcome with Magnesium sulphate - Jha, Rani; Verma, Sheela; Jha, Shailesh K (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: To determine the demographic characters of patients of eclampsia and the effectiveness of Magnesium Sulphate in terms of maternal and perinatal outcome. Methods: A prospective study of the eclamptic patients was conducted from 18th Aug - 17th Oct 2006 (1 Bhadra 2063 to 30 Ashwin 2063) attending the Obstetric Department of Janakpur Zonal Hospital (JZH). Results: Of the 50 eclamptic women [antepartum 80%, intrapartum 6 % and postpartum 14%] with overall improvement in 92% although 2 cases had to be referred to center with ICU facility and 2 cases died. The demographic characteristics were young primiparous population of low socioeconomic condtion. Caesarean was done for 48 %. Pretermaurity was seen in 50% and 76% were live birth. Conclusions: Nepal has a high maternal mortality rate and eclampsia is a big contributing factor, which could be reduced by using magnesium sulphate widely in all parts of Nepal taking, ours as one of the peripheral hospital as an example. Key words: Eclampsia, magnesium sulphate, maternal mortality doi:10.3126/njog.v2i1.1470 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 17 - 19 May -June 2007